Awareness and behaviour patterns regarding road safety measures among undergraduate students - Ratna, Harish V. K.; S. S., Rajesh; Jayaram, Ashok; M. S., Rajanna; P., Venkatesh; Iyengar, Krishna (International Journal Of Community Medicine And Public Health, 2017)
Background: In most regions of the world the global epidemic of traffic injuries is still increasing. In India motor vehicle population is growing at a faster rate than the economic and population growth. It has been estimated that unless immediate action is taken, road deaths will rise to the fifth leading cause of deaths by 2020.The present study was aimed to assess the level of awareness regarding road safety among the study participants and to study the behavior patterns while using motorized vehicles among the study participants. Methods: The present cross-sectional study was conducted in Sri Siddhartha Dental College, Tumkur. All Undergraduate students were included in the study. A total of 200 students were studied. They all drive either their own vehicles or others’ vehicles. They were aged from 17-27 years. The study period was from October 2016 to November 2016. Results: In total, 200 dental students were studied, ranging from 1st to final year BDS of age 17-27years; the mean age being 21.67 and standard deviation of 3.170.Only 148(74%) wear helmet and only 61(30.5%) interpreted Gap-In-Median correct. Conclusions: The awareness regarding road safety measures among the study participants was satisfactory but interpretation of traffic signs was poor-only 30.5% interpreted gap-in-median correct. The behavioral patterns among dental students are not satisfactory-only 74% of students wear helmet while riding, only 81.5% wear seat belts and 23.5% don’t follow lane rules while driving.